2021
DOI: 10.31557/apjcp.2021.22.9.2873
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Patient Navigator on Treatment Abandonment and Follow-up for High Grade Osteosarcoma Patients in the Philippine General Hospital

Abstract: Introduction: Treatment abandonment for osteosarcoma is a significant problem in developing countries with rates as high as 70%. This study aimed to determine the effect of a patient navigator on treatment abandonment and patient follow-up of osteosarcoma patients at a tertiary referral center. Materials and Methods: A retrospective review of osteosarcoma patients was performed investigating 2 cohorts based on the start of the patient navigator. Group 1 (Pre-Patient Navigator, n=46) were treated from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Across these studies, five reported using technology other than email or telephone calls. This included Google Hangouts and WhatsApp, 95 an online patient navigation tool, 96 social media and phone applications, 97 Zoom, 98 and web‐based tool and video conferencing 99 . Four implementation and feasibility studies were also included 95,100–102 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across these studies, five reported using technology other than email or telephone calls. This included Google Hangouts and WhatsApp, 95 an online patient navigation tool, 96 social media and phone applications, 97 Zoom, 98 and web‐based tool and video conferencing 99 . Four implementation and feasibility studies were also included 95,100–102 .…”
Section: Resultsmentioning
confidence: 99%
“…There were significant improvements in follow‐up and treatment adherence rates as well as attendance at cancer peer support groups after the implementation of patient navigation programs 97,116,117 . The inclusion of patient navigation for organizing appointments, orientating patients to tailored resources, coordinating team care, and establishing communication using social media applications from the time of diagnosis through to treatment reduced abandonment rates 117,118 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Timing of local control (LC) is not well studied in osteosarcoma; most protocols call for LC after two to three cycles of neoadjuvant chemotherapy; however, this could be delayed from the schedule for many reasons. In countries with limited resources, delays in LC may be due to the cost of prostheses, hesitancy to go for LC when the only feasible LC is amputation because of fear of stigma, and long waiting lists in government hospitals 22–24 . The impact of the delay of LC on survival outcomes in osteosarcoma is not well reported.…”
Section: Introductionmentioning
confidence: 99%
“…In countries with limited resources, delays in LC may be due to the cost of prostheses, hesitancy to go for LC when the only feasible LC is amputation because of fear of stigma, and long waiting lists in government hospitals. [22][23][24] The impact of the delay of LC on survival outcomes in osteosarcoma is not well reported.…”
Section: Introductionmentioning
confidence: 99%